Energy Economics: Growth, Resources, and Policies - Eden, Richard; Posner, Michael; Bending, Richard (Cambridge, England; New York: Cambridge University Press, 1981)
This book is structured in five parts, beginning with a discussion of the economics and technology of energy demand, and continuing in part two with a description of the main supply factors for hydro-carbons, nuclear energy and renewable energy resources. Part three is concerned with the market for energy, the structure of costs and prices, and the way in which the market is brought into balance. Part four considers the world energy outlook, taking account of the essential uncertainties of energy forecasting, and discusses energy prospects for different world regions. Part five entails the concluding chapters.
Includes index.
Includes bibliographical references: p. 423-432.
ne 20/04/2018
Loan
Keywords: Energy Policy; Power Resources